Social Statistics - Moore, Mel (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The focus of this course is the application of basic statistical techniques to sociologicalquestions. The goals of this course include developing an appreciation for the role ofstatistics in social research and everyday life, understanding the conceptual basis forstatistics, and the development of your ability to organize and present data using fundamental statistics.